Comparison of Alternative Molten Electrolytes for Water Splitting to Generate Hydrogen Fuel. Issue 10 (11th August 2016) - Licht, Stuart; Liu, Shuzhi; Cui, Baochen; Lau, Jason; Hu, Liwen; Stuart, Jessica; Wang, Baohui; El-Ghazawi, Omar; Li, Fang-Fang
Abstract : This study explores a new high temperature molten hydroxide domain to electrochemically split water into hydrogen fuel. Hydrogen fuel, if produced without greenhouse gas emissions, is a promising fuel for transportation. This study opens a pathway to low energy water splitting and the electrolytic production of hydrogen fuel without carbon dioxide emission. A wide range of pure and mixed alkali and alkali earth hydroxide electrolytes are explored at temperatures ranging from 200 to 700°C. Higher temperature leads to improved (lower voltage) water splitting and improved rates of charge transfer, but carries challenges (increased rates of parasitic side reactions as the molten electrolytes dehydrate with increasing temperature). This study extends the range of hydrogen formation in alkaline electrolysis water splitting to over 600°C, and demonstrates that lithium and/or barium hydroxide electrolytes remain hydrated at high temperatures, and in the high temperature domain are advantageous over sodium or potassium hydroxide electrolytes. In pure LiOH, the coulombic efficiency for hydrogen generation decreases with temperature and is measured respectively at ηH2 = 88%, 21%, 4% and 0%, respectively at 500, 600, 700 and 800°C.